Heated water and UV-C radiation to postharvest control of Cryptosporiopsis perennans on apples - Bartnicki, Vinícius Adão; Valdebenito-Sanhueza, Rosa Maria; do Amarante, Cassandro Vidal Talamini; de Castro, Luis Antônio Suita; Rizzati, Mara Regina; de Souza, João Antônio Vargas (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to assess the colonization of Cryptosporiopsis perennans in the epidermis of apples and the efficiency of heated water and UV-C radiation application to control this pathogen. In apples inoculated with C. perennans, the colonization of lenticels and adjacent areas by the pathogen was observed by electronic scanning microscopy. The sensitivity of C. perennans conidia was evaluated in aqueous suspension, at temperatures of 28, 45, 50 and 55°C for 15 and 30 s, and at UV-C radiation doses of 0.018, 0.037, 0.075, 0.150, 0.375, 0.750, 1.500 and 3.000 kJ m-2. The effects of UV-C radiation doses at 0.375, 0.750 and 1.500 kJ m-2 and heated water at 50°C, sprayed during 15 and 30 s were evaluated for controlling C. perennans in apples inoculated with the pathogen. The fungus produced abundant mycelium and conidia in lenticels and adjacent areas on the epidermis of the apples. The heated water at 50°C during 15 s and a 0.750 kJ m-2 UV-C radiation dose reduced conidia survival in more than 99%. Heated water sprayed at 50°C during 15 s and a UV-C radiation dose of 0.375 kJ m-2 control C. perennans in apples.